Apoplexy in Pregnancy (Indian Journal of Case Reports, 2022)
Headache during pregnancy is a common complaint in the emergency room. In pregnancy, pituitary disorders include both hormone active and hormone inactive tumors. Apoplexy may be the first clinical presentation of an underlying pituitary tumor. Red flag signs of presenting symptoms, to be assessed for identifying life-threatening etiology. Various pathophysiological mechanisms have been passed for pituitary apoplexy in pregnancy. Magnetic resonance imaging of the brain is the gold standard investigation. The mainstay of management is the initiation of steroids. Transnasal transsphenoidal removal of the tumor is the definitive treatment that requires a multidisciplinary approach. The indications of surgery are the presence of symptoms due to compression and endocrine abnormalities; however, gestational period should be taken into consideration. We report a case of headache in antenatal women who presented to our emergency room diagnosed with pituitary apoplexy managed with steroids and early surgery, and discharged with good clinical outcome. We recommend a methodical approach to common symptoms that assist in diagnosing forgotten etiology.